Effect of primary tumour resection without curative intent in patients with metastatic neuroendocrine tumours of the small intestine and right colon: meta-analysis. Issue 2 (23rd December 2021) - Van Den Heede, Klaas; Chidambaram, Swathikan; Van Slycke, Sam; Brusselaers, Nele; Warfvinge, Carl Fredrik; Ohlsson, Håkan; Nordenström, Erik; Almquist, Martin
Abstract: Background: Patients with small intestinal neuroendocrine tumours (siNETs) usually present with advanced disease. Primary tumour resection without curative intent is controversial in patients with metastatic siNETs. The aim of this meta-analysis was to investigate survival after primary tumour resection without curative intent compared with no resection in patients with metastatic siNETs. Methods: A systematic literature search was performed, using MEDLINE ® (PubMed), Embase ®, Web of Science, and the Cochrane Library up to 25 February 2021. Studies were included if survival after primary tumour resection versus no resection in patients with metastatic siNETs was reported. Results were pooled in a random-effects meta-analysis, and are reported as hazard ratios (HRs) with 95 per cent confidence intervals. Sensitivity analyses were undertaken to enable comment on the impact of important confounders. Results: After screening 3659 abstracts, 16 studies, published between 1992 and 2021, met the inclusion criteria, with a total of 9428 patients. Thirteen studies reported HRs adjusted for important confounders and were included in the meta-analysis. Median overall survival was 112 (i.q.r. 82–134) months in the primary tumour resection group compared with 60 (74–88) months in the group without resection. Five-year overall survival rates were 74 (i.q.r. 67–77) and 44 (34–45) per cent respectively. Primary tumour resection was associated with improved survival compared with no resection (HR 0.55, 95 per cent c.i. 0.47 to 0.66). This effect remained in sensitivity analyses. Conclusion: Primary tumour resection is associated with increased survival in patients with advanced, metastatic siNETs, even after adjusting for important confounders. Abstract : This meta-analysis showed better overall survival after primary tumour resection of small intestinal neuroendocrine tumours (siNETs) compared with non-surgical treatment in an advanced, incurable metastatic setting. This supports the mandatory involvement of surgeons in the decision-making and treatment of metastatic siNETs, even when surgery with curative intent is not possible.